Relationship of serum magnesium and vitamin d levels in a nationally-representative sample of iranian adolescents: The CASPIAN-III study - Roya Kelishadi; Ehsan Ataei; Gelayol Ardalan; Maryam Nazemian; Mohammadhasan Tajadini; Ramin Heshmat; Mojtaba Keikha; Mohammad Esmaeil Motlagh (International Journal of Preventive Medicine, 2014)
Background: This study aims to assess the relationship of serum Mg and vitamin D levels in a nationally-representative sample of Iranian adolescents. Methods: The study participants consisted of 330 students, aged range from 10 to 18 years, consisting of an equal number of individuals with and without hypovitaminosis D. The correlation between serum 25 hydroxy vitamin D (25(OH) D) and magnesium (Mg) concentrations was determined. Results: The mean age of participants was 14.74 ± 2.587 years, without significant difference between those with hypovitaminosis D and those without it. The mean 25(OH) D level was 6.34 ± 1.47 ng/ml in the group with hypovitaminosis D and 39.27 ± 6.42 ng/ml in the group without it. The mean Mg level was 0.80 ± 0.23 mg/dl with lower level in the group with hypovitaminosis D than in others (0.73 ± 0.22 mg/dl vs. 0.87 ± 0.22 mg/dl, respectively) and according to t-test analysis, significant lower levels in the deficient group was observed (P = 0.0001). The linear regression analysis showed the meaningful relationship between Mg and 25(OH) D serum levels (P = 0.0001). Conclusions: Our study revealed significant associations between serum Mg and 25(OH) D levels. This finding may be of use for further studies on the prevention and management of hypovitaminosis D in children and adolescents. Further longitudinal studies shall evaluate the underlying mechanisms and the clinical significance of the current findings.